Evaluation of the Implementation of Joint Business Group Assistance (KUBE) in Ternate City - Mohbir Umasugi; Muhlis Hafel (Publica: Jurnal Pemikiran Administrasi Negara, 2023)
The simplest evaluation when it can gather information about the circumstances before and after the KUBE program is implemented.  Ternate City itself received an allocation of 50 Joint Business Groups (KUBE) with a ratio of 5 companions where one companion has the task and responsibility of accompanying 10 groups because for 1 group there are 10 beneficiaries with details of assistance of 20 million for each group, it is necessary to evaluate the program assistance so that it can see the shortcomings to be corrected.  The data analysis method used in this study is descriptive qualitative. Descriptive qualitative is a method used to explore findings in the field. The results showed that one government program that requires community participation is the Joint Business Group (KUBE) program for the poor to increase Productive Economic Enterprises (UEP), especially in increasing income, providing some of the needs that are needed, creating harmony in social relations between citizens, and as a forum for sharing experiences between members. Forthis reason, the companion is very important in providing knowledge, skills and experience to the fostered KUBE group. In practice, KUBE companions will provide an understanding to each member of KUBE social assistance recipients that there must be a sense of belonging to run a joint business so that they are independent of the business they are running because through this program they can be helped to start a business as a first step to achieve social welfare and economic improvement in a better direction.